Transcriptional Profiling of STAT1 Gain-of-Function Reveals Common and Mutation-Specific Fingerprints - Giovannozzi, Simone; Demeulemeester, Jonas; Schrijvers, Rik; Gijsbers, Rik (Frontiers in Immunology, 2021)
STAT1 gain-of-function (GOF) is a primary immunodeficiency typically characterized by chronic mucocutaneous candidiasis (CMC), recurrent respiratory infections and autoimmunity. Less commonly, also immunodysregulation polyendocrinopathy enteropathy X-linked (IPEX)-like syndromes with CMC, and combined immunodeficiency without CMC have been described. Recently, our group and others have shown that different mutation-specific mechanisms underlie STAT1 GOF in vitro, including faster nuclear accumulation (R274W), and reduced mobility (R321, N574I) to near immobility in the nucleus (T419R) upon IFNγ stimulation. In this work, we evaluated the transcriptomic fingerprint of the aforementioned STAT1 GOF mutants (R274W, R321S, T419R, and N574I) relative to STAT1 wild-type upon IFNγ stimulation in an otherwise isogenic cell model. The majority of genes up-regulated in wild-type STAT1 cells were significantly more up-regulated in cells expressing GOF mutants, except for T419R. In addition to the common interferon regulated genes (IRG), STAT1 GOF mutants up-regulated an additional set of genes, that were in part shared with other GOF mutants or mutation-specific. Overall, R274W and R321S transcriptomes clustered with STAT1 WT, while T419R and N574I had a more distinct fingerprint. We observed reduced frequency of canonical GAS sequences in promoters of genes up-regulated by all the STAT1 GOF mutants, suggesting loss of DNA binding specificity for the canonical GAS consensus. Interestingly, the T419R mutation, expected to directly increase the affinity for DNA, showed the most pronounced effects on the transcriptome. T419R STAT1 dysregulated more non-IRG than the other GOF mutants and fewer GAS or degenerate GAS promotor sequences could be found in the promoter regions of these genes. In conclusion: our work confirms hyperactivation of common sets of IFNγ-induced genes in STAT1 GOF with additional dysregulation of mutation-specific genes, in line with the earlier observed mutation-specific mechanisms. Binding to more degenerate GAS sequences is proposed as a mechanism towards transcriptional dysregulation in R274W, R321S, and N574I. For T419R, an increased interaction with the DNA is suggested to result in a broader and less GAS-specific response. Our work indicates that multiple routes leading to STAT1 GOF are associated with common and private transcriptomic fingerprints, which may contribute to the phenotypic variation observed in vivo.